Práce manažera a uplatňování rovných příležitostí ve stavebnictví - Martincová, Tereza (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Diplomová práce pojednává o práci manažera a uplatňování rovných příležitostí ve stavebnictví. Cílem této diplomové práce je prozkoumání situace ve stavebních firmách a porovnání teorie s praxí. Teoretická část je věnována výkladu základních pojmů, které souvisí s tématem diplomové práce. Ve druhé, tedy praktické části, je na základě dotazníkového šetření zjištěn a vyhodnocen současný stav ve stavebních firmách. V závěru práce je provedeno posouzení teoretické a praktické části, navrhnuta doporučení a závěr diplomové práce.

The thesis deals with work of manager and the application of equal opportunities in the construction company. The aim of the thesis is to explore the situation in construction companies and comparison of theory with practise. The theoretical part introduces the basic terms and theories related to the topic. Based on a questionnaire survey, the practical part assesses the current situation in construction companies. In the end of the thesis is an evaluation theoretical and practical part, in order recommend prospective changes and conclusion of the thesis.
Managerial work and the application of equal opportunities in construction engineering
Keywords: Management; manažer; příležitost; rovné příležitosti; podnik; stavební podnik; Management; manager; opportunity; equal opprtunities; company; construction company